Unimpaired Responses to Vaccination With Protein Antigen Plus Adjuvant in Mice With Kit-Independent Mast Cell Deficiency - Schubert, Nadja; Lisenko, Katharina; Auerbach, Christian; Weitzmann, Anke; Ghouse, Shanawaz Mohammed; Muhandes, Lina; Haase, Christa; Häring, Tobias; Schulze, Livia; Voehringer, David; Gunzer, Florian; Müller, Werner; et al. (Frontiers in Immunology, 2018)
Innate inflammatory responses are crucial for induction and regulation of T cell and antibody responses. Mast cell (MC)-deficient Kit mutant mice showed impaired adaptive immunity, suggesting that MCs provide essential adjuvant activities, and pharmacological MC activation was proposed as a new adjuvant principle. However, the Kit mutations result in complex alterations of the immune system in addition to MC deficiency. We revisited the role of MCs in vaccination responses using Mcpt5-Cre R26DTA/DTA and Cpa3Cre/+ mice that lack connective tissue MCs or all MCs, respectively, but feature an otherwise normal immune system. These animals showed no impairment of T and B cell responses to intradermal vaccination with protein antigen plus complete Freund’s adjuvant. Moreover, we demonstrate that the adjuvant effects of the MC secretagogue c48/80 in intradermal or mucosal immunization are independent of the presence of MCs. We hence find no evidence for a regulation by MCs of adaptive immune responses to protein antigens. The finding that immunological MC functions differ from those suggested by experiments in Kit mutants, emphasizes the importance of rigorous tests in Kit-independent MC-deficiency models.